Peran Badan Penanggulangan Bencana Daerah Dalam Penanggulangan Banjir Rob Di Desa Wilayah Pesisir Kecamatan Kandanghaur Kabupaten Indramayu - Fitriyah, Ayu; Ismanudin; Soleh (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
The tidal floods that often hit Kandanghaur Subdistrict require the involvement of the Indramayu District Disaster Management Agency (BPBD) in mitigation efforts. Therefore, this study aims to determine the role of the Indramayu District BPBD as a regulator, dynamizer, and facilitator in mitigating tidal floods in the villages of Eretan Wetan and Eretan Kulon, as well as to identify the inhibiting factors. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results show that BPBD has carried out its role as a regulator, facilitator, and dynamizer in tidal flood mitigation. In its role as a regulator, there is already a clear legal basis and implementing organization for tidal flood mitigation. The role as a catalyst has been carried out through the dissemination and training of the Destana program to the community. Meanwhile, the role as a facilitator is carried out through assistance and the provision of aid or facilities in the form of evacuation, the establishment of command posts and public kitchens, as well as the preparation of Jitupasna documents and Rehabilitation and Reconstruction Plan documents. However, the implementation of these roles has not been optimal due to constraints such as limited budgets, low community participation, inter-agency coordination challenges, and social and cultural resistance from the community.